Administrative Appeal Efforts in Indonesian Administrative Dispute Resolution After the Government Administration Law (Pre-Omnibus Law) - Muhammad Rizal Sirojudin (Ahmad Dahlan Legal Perspective, 2022)
Administrative effort is an effort to resolve disputes in the Indonesian State Administrative Court. This administrative effort changed after the Omnibus Law was introduced. However, the Omnibus Law itself will be changed in the future because there is a demand for a constitutional court decision. Therefore, administrative efforts have the potential to change back to what it was before the Omnibus Law. This study aims to determine the competence of existing changes in administrative efforts. This research method is carried out using a normative approach that is based on browsing library materials or secondary data. The result to be achieved in this research is to give a prescription that Law Number 30 of 2014 concerning Government Administration has its own procedural process, even though this Law is sectoral.